Influence of Digital Technology on Arabic Language Learning in the Modern Era: English - Okta Taufika Rahma; Moh. Ismail (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
Digital technology on Arabic language learning in the modern era. Along with the development of technology, Arabic language learning methods have undergone significant changes, including the use of interactive learning applications, e-learning platforms, and social media. Digital technology not only facilitates access to learning materials but also enhances the effectiveness of the learning process. This study explores how the integration of technology in Arabic language learning can increase students' motivation, participation, and learning outcomes. On the contrary, difficulties like such as the lack of direct interaction and the potential digital divide are also discussed. The results show that although digital technology brings significant positive impacts, It is crucial to maintain a balance between the use of technology and traditional learning.